Analisis Logika, Riset, Kebenaran Dalam Pendidikan di Indonesia - Wiwi Uswatiyah; Siti Aminah; Sofyan Sauri; Faiz Karim Fatkhulah (Jurnal Dirosah Islamiyah, 2021)
The digital era provides its own meaning and consequences for the morale of the leadership group. This study aims to analyze the morals of Islamic leadership groups in the digital era based on a review of philosophy, psychology and sociology. A leader in the digital era is required to be compatible with the demands and needs of the times. Philosophically, the morale of the leadership group provides reinforcement in decision making or policy formulation. Psychologically, group morals give its own color to aspects of personality. Leaders must be able to influence their members so that they can jointly run the organization. Sociologically, the moral of the leadership group has similarities with the religious foundation. Everyone is required to be able to have and practice good group morals in various conditions. This kind of leadership is expected by many people. The challenge of social education leaders today is very hard to be able to provide awareness to students and educationists to be able to socialize and get used to completely online work.